Growth of Drimys brasiliensis in the Araucaria Forest, Colombo, State of Parana, Brazil Crescimento de Drimys brasiliensis na Floresta Ombrófila Mista, Colombo, PR - Mariana Ferraz de Oliveira (Pesquisa Florestal Brasileira, 2010)
Drimys brasiliensis Miers, locally know as cataia or casca-d´anta, is a Winteraceae, common in Araucaria Forest, and considered an important species in management and conservation plans. Due to its relevance, it is important to obtain information about its development and growth, which was the main objective of the present work. Non destructive samples were collected from adult trees of Drimys brasiliensis, in a secondary forest, located in Colombo, Parana State, Brazil. It was observed average annual diametric increment of 0.32 cm, and 0.01 m² of average annual transversal area increment. doi: 10.4336/2010.pfb.30.61.79 Drimys brasiliensis Miers, conhecida como cataia ou casca-d’anta, é uma espécie da família Winteraceae, típica da Floresta Ombrófila Mista (FOM) e considerada como uma espécie muito importante em planos de manejo e conservação. Devido a isso, buscam-se novas informações sobre seu desenvolvimento e crescimento, objetivo principal do presente trabalho. Foram coletadas amostras não destrutivas de dez árvores adultas de Drimys brasiliensis, em uma floresta secundária localizada no Município de Colombo, Estado do Paraná. Observou-se 0,32 cm de incremento diamétrico anual médio, representando 0,01 m² de incremento anual médio em área transversal. doi: 10.4336/2010.pfb.30.61.79